Familial Hypercholesterolemia Screening in a Cardiac Rehabilitation Program After Myocardial Infarction - Carlos Bertolín-Boronat; Víctor Marcos-Garcés; Héctor Merenciano-González; María Luz Martínez Mas; Josefa Inés Climent Alberola; Nerea Perez; Laura López Bueno; María Concepción Esteban Argente; María Valls Reig; Ana Arizón Benito; Alfonso Payá Rubio; César Ríos-Navarro; et al. (Cardiogenetics)
Familial hypercholesterolemia (FH) is relatively prevalent in myocardial infarction (MI) sufferers, and its diagnosis could improve preventive treatment in family members. We aim to analyze the diagnosis of FH and the rate of genetic testing in a prospective cohort of 245 patients submitted to our Cardiac Rehabilitation Program (CRP) after MI. Baseline characteristics were registered, and basal low-density lipoprotein cholesterol (LDL-C) was calculated after correction for lipid-lowering therapies (LLT) before or during admission. Simplified Dutch Lipid Clinic Network Scores (sDLCNS) were retrospectively calculated based on personal and familial history of premature cardiovascular disease and basal LDL-C levels. Mean age was 62.19 ± 13.93 years, and most patients were male (81.6%). Mean LDL-C before admission and basal LDL-C corrected for LLT were 131.79 ± 45.34 mg/dL and 162.87 ± 44.17 mg/dL, respectively. Patients in the cohort were retrospectively categorized in the “unlikely” (<3 points; n = 162, 66.1%), “possible” (3–5 points; n = 72, 29.4%) and “probable” (6–8 points; n = 11, 4.5%) sDLCNS categories. Genetic testing for FH was requested in four (1.6%) patients, and no clinically significant genetic variants were detected. Patients who underwent genetic testing depicted significantly higher basal LDL-C (233 ± 49.09 vs. 161.71 ± 43.25 mg/dL, p = 0.001). However, the rate of individuals undergoing genetic testing was negligible even in the “possible” (n = 2, 2.8%) and “probable” (n = 1, 9.1%) sDLCNS categories. In conclusion, genetic testing for FH in our CRP after MI is largely underutilized, even in patients with a “possible” or “probable” diagnosis based on sDLCNS criteria, which represent about a third of the cohort. Strategies to improve screening for FH should be prospectively implemented.